Negotiating Thainess and Malayness: Literary Hybridity, Sacred Geography, and Epistemic Resistance in Patani - Aini, Tri Hermawan (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
What happens when a people write their nation back into existence? In Thailand’s southern border region of Patani, where Malay-Muslims have endured a century of assimilation under Thainess, literature functions as sovereignty by other means. This article examines how two classical Malay chronicles: Hikayat Patani and Sejarah Kerajaan Melayu Patani operate as forces of epistemic resistance against the Thai state’s homogenizing narrative. Drawing on postcolonial theory, cultural memory, and Indigenous studies, the analysis reveals four mechanisms of literary defiance: cultural memory as sovereign historiography, hybridity as a Third Space between Thainess and Malayness, script politics as symbolic capital (Jawi versus Thai), and sacred geography as indigenous belonging mapped onto tanah amanah (sacred trust). Patani’s literature actively constructs identity through genealogies that bypass Bangkok, narrative framings that recast defeat as divine test, and the quiet persistence of Jawi script. Unlike security-focused scholarship that frames Patani’s struggle through violence alone, this article argues that literature constitutes a more fundamental battleground: the struggle over meaning, memory, and the right to narrate one’s own past.